The Simple Game of the Learning Model Approach on Elementary School Students - Muhammad Syam’un Al Ghazi; Kholid (UNIB Press, 2023)
This study aims to produce a product model of learning devices through a simple game to improve the speed and agility of upper grade of elementary school students, as well as determine the feasibility and effectiveness of learning device models through simple games.This learning device model was developed to be used by upper grade elementary school students, during PJOK learning, so that upper grade elementary school students are able to maintain speed and agility performance during PJOK learning. The method used in this research is a research and development method ( Research and Development) the Borg & Gall model which reviews problems, data collection, product design, design validation, design revisions, product trials, product revisions, usage trials, product revisions, and dissemination. The subjects of this study were PJOK teachers and elementary school students. The trials carried out included two stages, namely small-scale trials conducted on one PJOK teacher with 20 students, large-scale trials with two PJOK teachers with 40 students, and an effectiveness test with two PJOK teachers with 40 students. Based on the findings of the data and analysis, the researcher describes several parts of the findings through the validation assessment of material experts, obtaining an average rating of 3.83 in the